An investigation into the left side of green human resource management - Ampofo, Emmanuel Twumasi; Karatepe, Osman M. (Springer Nature, 2024)
A major issue confronting humanity in the world today is global climate change Climate change. What appears the certainty is that the world is becoming an unsafe place for human existence due to the increasing rate of degradation to the environment. It is obvious that companies are a major contributor to climate warming. In 2017, it was reported that only 100 companies have contributed to over 71% of greenhouse gas emission in the world since 1988. However, there has been inspiring efforts by some companies to change the narrative. In recent times, many global firms have critically assessed their environmentalism and are therefore adopting several pro-environmental policies and practices such as green supply chains, green finance, and green marketing. In the management literature, green human resource management Green Human Resource Management (HRM) has gained significant attention because of its immense role in helping companies to obtain sustainable Sustainable competitive urge. A careful search in the green HRM Green HRM literature reveals that the construct has been linked to several outcome variables including turnover and organizational citizenship behavior. However, just a few antecedents of green HRM Green HRM have been identified in the pertinent literature. These include corporate social responsibility Corporate social responsibility, top management commitment, and intellectual capital. In this chapter, we discuss other potential key predictors of green HRM Green HRM. Based on relevant theoretical underpinnings, this chapter identifies several personal, organizational, and environmental variables that affect green HRM Green HRM. Thus, this piece does not only broaden knowledge regarding the antecedents of green HRM Green HRM but also emphasizes the importance of personality and context in influencing the acceptance and implementation of eco-friendly practices in organizations Organizations. © Springer Nature Singapore Pte Ltd. 2024. All rights reserved.
Keywords: Environmental sustainability; Environmental variables; Green human resource management; Organizational variables; Personal variables